Financial Development and Dynamic Investment Behavior : Evidence from Panel Vector Autoregression - Love, Inessa; Zicchino, Lea (World Bank, Washington, DC, 2014)
The authors apply vector autoregression to firm-level panel data from 36 countries to study the dynamic relationship between firms' financial conditions and investment. They argue that by using orthogonalized impulse-response functions they are able to separate the "fundamental factors" (such as marginal profitability of investment) from the "financial factors" (such as availability of internal finance) that influence the level of investment. The authors find that the impact of the financial factors on investment, which they interpret as evidence of financing constraints, is significantly larger in countries with less developed financial systems. The finding emphasizes the role of financial development in improving capital allocation and growth.